Dinamika Penyelesaian Perselisihan Pemutusan Hubungan Kerja Sepihak Melalui Litigasi dengan Pembayaran Uang Pisah (Studi Kasus Putusan Pengadilan Hubungan Industrial Pada Pengadilan Negeri Pekanbaru Nomor 80/Pdt.Sus-Phi/2021/Pn Pbr) - Try Nurwantoko, Endro; Lie, Gunardie; Rizqy Syailendra, Moody (Universitas Ekasakti, 2023)
This study aims to examine the dynamics of resolving disputes arising from unilateral termination of employment (PHK) through litigation involving severance pay. This case study analyzes the Decision of the Industrial Relations Court at the District Court of Pekanbaru Number 80/Pdt.Sus-PHI/2021/PN Pbr. The research method employed is empirical research, involving the analysis of legal documents and data examination. The research findings reveal factors influencing the resolution of such cases, including applicable legal provisions, judicial considerations, and legal strategies employed by the parties involved in the litigation. Additionally, the study also scrutinizes the social and economic impacts of severance pay in the context of unilateral employment termination. The implications of these research findings are expected to provide insights for legal practitioners, companies, and employees in addressing similar situations in the future.